1985
DOI: 10.1111/j.1600-0714.1985.tb00543.x
|View full text |Cite
|
Sign up to set email alerts
|

A histological analysis of the early effects of alcohol and tobacco usage on human lingual epithelium

Abstract: Macroscopically normal tongues were examined from 161 necropsies. Two types of lingual epithelium were investigated by morphometry and the results were statistically analysed in relation to known levels of alcohol and tobacco usage in each case. Alcohol and tobacco were each associated with a reduction in epithelial thickness brought about by a reduction in the maturation layer due mainly to cell shrinkage By contrast, the progenitor layer increased in size, due to hypertrophy rather than hyperplasia Changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 17 publications
2
29
1
2
Order By: Relevance
“…This finding differs from those reported in previous studies, which found higher proliferative activity in the suprabasal layer cells of dorsal tongue epithelium (Valentine et al, 1985;Maier et al, 1994;Maito et al, 2003;Carrard et al, 2004). This difference could be explained by the models used (rats instead of mice), since different animal models appear to have differential sensitivity to alcohol (Tabakoff & Hoffman, 2000).…”
Section: Dorsal Tongue Epitheliumcontrasting
confidence: 95%
See 4 more Smart Citations
“…This finding differs from those reported in previous studies, which found higher proliferative activity in the suprabasal layer cells of dorsal tongue epithelium (Valentine et al, 1985;Maier et al, 1994;Maito et al, 2003;Carrard et al, 2004). This difference could be explained by the models used (rats instead of mice), since different animal models appear to have differential sensitivity to alcohol (Tabakoff & Hoffman, 2000).…”
Section: Dorsal Tongue Epitheliumcontrasting
confidence: 95%
“…This finding corroborates the results of studies that found an increased cell proliferation in the tongue epithelium of mice after longer intake periods (Maito et al, 2003;Carrard et al, 2004). Valentine et al (1985) found an increase in the thickness of the proliferative compartment of the tongue epithelium in humans that usually consume alcohol.…”
Section: Ventral Tongue Mucosasupporting
confidence: 91%
See 3 more Smart Citations